2021
DOI: 10.1177/00302228211048316
|View full text |Cite
|
Sign up to set email alerts
|

Nobody Should Die Alone. Loneliness and a Dignified Death During the COVID-19 Pandemic

Abstract: During the direst months of the COVID-19 pandemic, thousands of people died alone. This study analyzes these deaths, which occurred without the presence of loved ones, and seeks to a) examine the significance for relatives, as well as professionals, of dying alone, b) determine if these solitary deaths can be considered dignified, or good deaths, and c) evaluate if the treatment of the cadavers and the funeral rites transpired with the desired dignity and sensitivity. The study was carried out in the autonomou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 28 publications
1
6
0
Order By: Relevance
“…This current study also found that the highest impact on ICU staff resulted from the fact that patients died alone. This finding is also shown in other studies which report that this fact lacked the desired dignity, and the burden was higher for relatives even though ICU staff did their best to accompany and dignify death 32 33…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…This current study also found that the highest impact on ICU staff resulted from the fact that patients died alone. This finding is also shown in other studies which report that this fact lacked the desired dignity, and the burden was higher for relatives even though ICU staff did their best to accompany and dignify death 32 33…”
Section: Discussionsupporting
confidence: 75%
“…This finding is also shown in other studies which report that this fact lacked the desired dignity, and the burden was higher for relatives even though ICU staff did their best to accompany and dignify death. 32 33 …”
Section: Discussionmentioning
confidence: 99%
“…The COVID-19 pandemic altered processes related to care of dying patients and subsequent death. Hernández-Fernández and Meneses-Falcón 9 conducted a qualitative, phenomenological study between March and May 2020 in Spain that included a variety of professionals (N = 34), including hospital and emergency room nurses, informants, and relatives. The major theme was that dying alone is not considered a good death and has social significance.…”
Section: Review Of the Literaturementioning
confidence: 99%
“…Healthcare providers, globally, have struggled to safeguard the dignity of the sick and dying, which is one of the most important goals of end-of-life care. 18 During the webinar, speakers noted that limited visitation hours due to public health restrictions, the absence of loved ones at the time of death, and obstructed communication through layers of personal protective equipment (PPE) have led to patients dying in seclusion, thereby undermining their sense of dignity and increasing depersonalization. 19 Zambrano Hellion Hospital in Mexico, at the height of the pandemic, survival was often prioritized over humanity.…”
Section: Dignitymentioning
confidence: 99%